The extrafollicular response is sufficient to drive initiation of autoimmunity and early disease hallmarks of lupus - Voss, Lasse F.; Howarth, Amanda J.; Wittenborn, Thomas R.; Hummelgaard, Sandra; Juul-Madsen, Kristian; Kastberg, Kristian S.; Pedersen, Mathias K.; Jensen, Lisbeth; Papanastasiou, Anastasios D.; Vorup-Jensen, Thomas; Weyer, Kathrin; Degn, Søren E. (Frontiers in Immunology, 2022)
Introduction Many autoimmune diseases are characterized by germinal center (GC)-derived, affinity-matured, class-switched autoantibodies, and strategies to block GC formation and progression are currently being explored clinically. However, extrafollicular responses can also play a role. The aim of this study was to investigate the contribution of the extrafollicular pathway to autoimmune disease development. Methods We blocked the GC pathway by knocking out the transcription factor Bcl-6 in GC B cells, leaving the extrafollicular pathway intact. We tested the impact of this intervention in two murine models of systemic lupus erythematosus (SLE): a pharmacological model based on chronic epicutaneous application of the Toll-like receptor (TLR)-7 agonist Resiquimod (R848), and 564Igi autoreactive B cell receptor knock-in mice. The B cell intrinsic effects were further investigated in vitro and in autoreactive mixed bone marrow chimeras. Results GC block failed to curb autoimmune progression in the R848 model based on anti-dsDNA and plasma cell output, superoligomeric DNA complexes, and immune complex deposition in glomeruli. The 564Igi model confirmed this based on anti-dsDNA and plasma cell output. In vitro, loss of Bcl-6 prevented GC B cell expansion and accelerated plasma cell differentiation. In a competitive scenario in vivo, B cells harboring the genetic GC block contributed disproportionately to the plasma cell output. Discussion We identified the extrafollicular pathway as a key contributor to autoimmune progression. We propose that therapeutic targeting of low quality and poorly controlled extrafollicular responses could be a desirable strategy to curb autoreactivity, as it would leave intact the more stringently controlled and high-quality GC responses providing durable protection against infection.